Sharing privately: the effect publication on social media has on expectations of privacy. Issue 1 (2nd January 2017) - Mills, Max
ABSTRACT: Users of social media wish to share information with their friends. They want to tell them about their thoughts, feelings and, more commonly, what they are having for dinner. Yet, they do not want to tell these things to the whole world. Under the tort of misuse of private information the desire to share privately is something of a paradox. There are two reasons for this: the threshold of when information is deemed to be in the public domain is too low; and, second, the protection afforded to someone who is deliberately seeking publicity is too little. English law is currently incapable of protecting those who share on social media from having their information disseminated further than they intend. There are however options for reform, which include an application of the law of confidence, copyright and, more radically, a fundamental change to the concept of privacy itself.